Phase diagrams of the Bose-Hubbard model at finite temperature - Stasyuk, I.V.; Mysakovych, T.S. (Condensed Matter Physics, 2009)
The phase transitions in the Bose-Hubbard model are investigated. A single-particle Green's function is calculated in the random phase approximation and the formalism of the Hubbard operators is used. The regions of existence of the superfluid and Mott insulator phases are established and the (μ, t) (the chemical potential transfer parameter) phase diagrams are built. The effect of temperature change on this transition is analyzed and the phase diagram in the (T, μ) plane is constructed. The role of thermal activation of the ion hopping is investigated by taking into account the temperature dependence of the transfer parameter. The reconstruction of the Mott-insulator lobes due to this effect is analyzed. Дослiджено фазовi переходи в моделi Бозе-Хаббарда. Одночастинкова функцiя Грiна розрахована в наближеннi хаотичних фаз iз використанням формалiзму операторiв Хаббарда. Встановлено областi iснування надплинної фази та фази моттiвського дiелектрика i побудовано фазовi дiаграми в площинi (; t). Проаналiзовано вплив змiни температури на фазовi переходи та побудовано фазовi дiаграми в площинi (T; ). Дослiджено випадок термiчної активацiї перескоку частинок та проаналiзовано перебудову фазових дiаграм у цьому випадку.